Intensive structured education for type 1 diabetes management using BERTIE: Long-term follow-up to assess impact on glycaemic control and quality of life indices. (September 2018) - Humayun, Malik Asif; Jenkins, Emma; Knott, Julia; Ryder, Jacky; Shaban, Clare; Weiss, Melanie; Charman, Julie; Cavan, David; Brooks, Augustin
Highlights: Long term outcomes from BERTIE structured education for type 1 diabetes management. Glycated haemoglobin (HbA1c) and PAID score improved, severe hypoglycaemia reduced. HbA1c improvement is maintained for up to five years following course attendance. Abstract: Aims: Bournemouth Type 1 Intensive Education (BERTIE) is a structured education course delivered 1 day a week for 4 weeks for self-management of type 1 diabetes. BERTIE outcomes were analysed to assess long-term effectiveness: primary outcome assessed impact of BERTIE on glycaemic control, secondary outcomes assessed impact on Problem Area in Diabetes (PAID) scale, severe hypoglycaemia and diabetic ketoacidosis incidence (DKA). Methods: Prospectively collected outcome data from attendees included glycated haemoglobin (HbA1c), PAID, severe hypoglycaemia and DKA incidence recorded pre-course, 6 months and 1 year post-attendance, with HbA1c assessed annually at subsequent clinic visits. Results: Between 1999 and 2015, 524 people attended BERTIE with 5 year follow-up in 316 (60.3%) attendees. HbA1c was reduced from 74 ± 17 mmol/mol (8.9 ± 1.6%) at baseline to 71 ± 15 mmol/mol (8.6 ± 1.4%) at 1 year and 70 ± 15 mmol/mol (8.6 ± 1.3%) at 5 years (p < 0.0001); severe hypoglycaemia incidence reduced from 0.8 ± 2.1 to 0.4 ± 2.2 episodes/person/year at 1 year (p < 0.0001); PAID scale reduced from 23 ± 16 to 15 ± 12 (p < 0.0001) at 1 year; DKA incidence was 0.06 ± 0.34 episodes/person/year pre-course and 0.03 ± 0.21 at 1 year (p = 0.5271). Conclusions: BERTIE outcome data demonstrate favorable biochemical and psychological outcomes supporting recommendations that structured education be provided to adults with type 1 diabetes.